Pemanfaatan Limbah Onggok Aren sebagai Bahan Baku Pupuk Kompos Menggunakan Aktivator EM-4 dan Molase sebagai Upaya Pemberdayaan Masyarakat Daleman, Klaten - Nurgirisia, Novesa; Margono, Margono; Waluyo, Joko; Agung Wibowo, Wusana; Herwi Pranolo, Sunu; Siswahjono Tatag Sembodo, Bregas; Diana Susanti, Ari (Politeknik Negeri Jember, 2026)
Arenga palm flour–producing regions face significant challenges in managing solid waste, particularly in Daleman Village, Klaten, Central Java. Home-scale industries generate onggok aren, a cellulose-rich residue consisting of pulp and coarse fibers produced in large quantities. However, in practice, this waste is often discharged directly into rivers, contributing to water and environmental pollution. Most areas of Daleman Village are agricultural lands that typically require fertilizers to maintain soil fertility, which encourages further exploration of the potential use of onggok aren waste. One promising utilization is as a raw material for compost fertilizer that is both efficient and affordable. The composting process is carried out using a simple method with the aid of the EM4 bioactivator and molasses to accelerate the decomposition of organic materials. The activator mixture is applied in a specific ratio of 1 part EM4, 1 part molasses, and 10 parts water. Utilizing onggok aren waste as compost fertilizer not only addresses the issue of waste accumulation but also enhances the value of natural resources and reduces dependence on chemical fertilizers.